The contested rewe : sacred sites, misunderstandings, and ontological pluralism in M apuche land negotiations - Di Giminiani, Piergiorgio (The Journal of the Royal Anthropological Institute, 2013)
Sacred sites lie at the core of indigenous peoples' land claims and negotiations with the state. These sites are often subject to accusations of inauthenticity by state actors, which potentially lead to the delegitimization of claims over ancestral land. This article argues that misunderstandings in M apuche land negotiations in C hile do not originate as strategic refusals to understand, but rather in a form of understanding which aims to make radical differences commensurable within the logics of statecraft and national society. In the process of cultural translation, the ontological principles that make certain places sacred in the M apuche lived world are not recognized, resulting in the transformation of these sites into symbols of identity strategically employed for political ends.